Characterising meaningful patient and public involvement in the pharmaceutical industry research setting: a retrospective quality assessment - Jennifer Preston; Natalie Bohm; Adit Bassi; Angela Davies; Kamil Sterniczuk; Berkeley Phillips; Sally-Anne Dews; Sean Buckland; Lucy Clements; Rachel Daley; Sophie Evett; Samantha Howland; et al. (BMJ Open, 2023)
Objectives Patient and public involvement (PPI) in clinical research has a well-established infrastructure in the UK, and while there has been good progress within pharmaceutical-industry-sponsored research, further improvements are still needed. This review aims to share learnings from quality assessments of historical PPI projects within Pfizer UK to inform future projects and drive PPI progress in the pharmaceutical industry.Design and setting Internal assessments of Pfizer UK PPI projects were conducted to identify all relevant projects across the medicines development continuum between 2017 and 2021. Five sample projects were developed into case studies.Outcome measure Retrospective quality assessments were performed using the Patient Focused Medicines Development (PFMD) Patient Engagement Quality Guidance (PEQG) tool. Recommendations for improvement were developed.Results Retrospective case study analysis and quality framework assessment revealed benefits of PPI to both Pfizer UK and to external partners, as well as challenges and learnings to improve future practice. Recommendations for improvement based on these findings focused on processes and procedures for PPI, group dynamics and diversity for PPI activities, sharing of expertise, the importance of bidirectional and timely feedback, and the use of understandable language in materials.Conclusions PPI in medicines development is impactful and beneficial but is still being optimised in the pharmaceutical industry. Using the PFMD PEQG tool to define gaps, share learnings and devise recommendations for improvement helps to ensure that PPI is genuine and empowering, rather than tokenistic. Ultimately, these recommendations should be acted on to further embed PPI as an integral part of medicines development and health research within the pharmaceutical industry. This article includes a plain language summary in the supplement.